2006
DOI: 10.1021/tx0502443
|View full text |Cite
|
Sign up to set email alerts
|

Lung DNA Adducts Detected in Human Smokers Are Unrelated to Typical Polyaromatic Carcinogens

Abstract: Several studies have reported the presence of DNA adducts derived from benzo(a)pyrene and other polyaromatics by 32P-postlabeling/TLC by measuring diagonal radioactive zones (DRZs) in lung tissues of human smokers. However, our experimental studies in rodent models, which used modified chromatographic conditions to obtain distinct adduct spots, suggested that cigarette smoke-related lipophilic DNA adducts may not be derived from polycyclic aromatic hydrocarbons (PAHs) or aromatic amines. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…Gupta laboratory (35) recently reported that the majority of diagonal radioactive zones (DRZs) detected in cigarette smokers using 32 P post-labeling and 2 dimensional thin layer chromatograph (2D-TLC) method are not PAHs and aromatic amines. Interestingly, these workers also found that DNA modified with acetyl aldehydes and formaldehydes produced the same DRZs as DNA from lung tissues of cigarette smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta laboratory (35) recently reported that the majority of diagonal radioactive zones (DRZs) detected in cigarette smokers using 32 P post-labeling and 2 dimensional thin layer chromatograph (2D-TLC) method are not PAHs and aromatic amines. Interestingly, these workers also found that DNA modified with acetyl aldehydes and formaldehydes produced the same DRZs as DNA from lung tissues of cigarette smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Disadvantages include lack of chemical specificity, particularly in 32 P-postlabeling analyses, and difficulty in quantitation. Although the adducts detected using this method are often referred to in the literature as "aromatic DNA adducts", there is strong evidence that they are not related to PAH (63). The application of these methods to tissues obtained from smokers has been extensively reviewed (61).…”
Section: Tobacco Carcinogen Biomarkersmentioning
confidence: 99%
“…They found that the "G/G" genotype of rs402710 was associated with significantly higher levels of DNA adducts (p=0.02). High levels of bulky aromatic and/or hydrophobic DNA adducts in lung tissue from smokers are formed by DNA-binding polycyclic aromatic hydrocarbons (PAHs) and by aldehydes found in cigarette smoke [34,35]. Smokingrelated DNA adducts can lead to mutation of key genes, such as TP53, and ultimately result in tumor development [36].…”
Section: Discussionmentioning
confidence: 99%